Radiation‐constrained boundaries cause nonuniform responses of the carbon uptake phenology to climatic warming in the Northern Hemisphere. Issue 3 (7th November 2022) - Descals, Adrià; Verger, Aleixandre; Yin, Gaofei; Filella, Iolanda; Fu, Yongshuo H.; Piao, Shilong; Janssens, Ivan A.; Peñuelas, Josep
Abstract: Climatic warming has lengthened the photosynthetically active season in recent decades, thus affecting the functioning and biogeochemistry of ecosystems, the global carbon cycle and climate. Temperature response of carbon uptake phenology varies spatially and temporally, even within species, and daily total intensity of radiation may play a role. We empirically modelled the thresholds of temperature and radiation under which daily carbon uptake is constrained in the temperate and cold regions of the Northern Hemisphere, which include temperate forests, boreal forests, alpine and tundra biomes. The two‐dimensionality of the temperature‐radiation constraint was reduced to one single variable, θ, which represents the angle in a polar coordinate system for the temperature‐radiation observations during the start and end of the growing season. We found that radiation will constrain the trend towards longer growing seasons with future warming but differently during the start and end of season and depending on the biome type and region. We revealed that radiation is a major factor limiting photosynthetic activity that constrains the phenology response to temperature during the end‐of‐season. In contrast, the start of the carbon uptake is overall highly sensitive to temperature but not constrained by radiation at the hemispheric scale. This study thus revealed that while at the end‐of‐season the phenology response to warming is constrained at the hemispheric scale, at the start‐of‐season the advance of spring onset may continue, even if it is at a slower pace. Abstract : The constraint of temperature and radiation on vegetation productivity was estimated with the variable θ . Values of θ differ during the start and end of season (SoS and EoS), indicating that radiation constraints the trend towards longer growing seasons but differently during spring and autumn. While the phenology response to future warming is overall constrained at the end of season, the advance of spring onset may continue.